Управління конкурентоспроможністю підприємства як основа сталого розвитку - Козак,К.Б.; Бакай, Р.В.; Буряченко, Ю.М. (Економічний вісник Донбасу, 2025)
У статті розглянуто актуальні підходи до управління конкурентоспроможністю підприємства в умовах трансформації ринкового середовища. Основну увагу приділено переходу від традиційного ресурсно-орієнтованого управління до стратегічно-орієнтованої моделі, яка ґрунтується на прогнозуванні змін і використанні ефективних управлінських інструментів. Проаналізовано вплив впровадження сучасних моделей (модель життєвого циклу продукту, модель п’яти сил конкуренції М. Портера, модель створення цінності для клієнта) та систем управління (стратегічне планування, контроль і моніторинг, управління якістю та ризиками) на забезпечення сталого розвитку підприємства. Підкреслено, що конкурентоспроможність є не лише результатом ефективної стратегії, а й її критерієм, що визначає довгострокову стійкість бізнесу. Запропоновано концепцію сталого розвитку підприємства, яка базується на ідеї гармонізації трьох ключових компонентів: економічної ефективності, екологічної безпеки та соціальної відповідальності. Особливу увагу приділено взаємозв’язку між ефективним управлінням конкурентоспроможністю та досягненням цілей сталого розвитку, що забезпечує стратегічну цінність розвитку підприємства в довгостроковій перспективі. This article explores contemporary approaches to managing enterprise competitiveness in dynamic market transformations. It emphasizes the paradigm shift from traditional resource-oriented management to a forward-looking, strategically oriented model. This modern approach prioritizes forecasting market changes and leveraging advanced managerial tools to enhance enterprises' adaptability and resilience. The study analyzes the application of key management models – such as the product life cycle model, Michael Porter’s five competitive forces framework, and the customer value creation model – as well as comprehensive management systems, including strategic planning, monitoring and evaluation, quality management, and risk management systems. These elements are integral to sustainable enterprise development in a complex and volatile business environment. The article's central argument is that competitiveness should be viewed not only as the result of a successful strategy but also as a defining criterion of long-term business sustainability. The research introduces a conceptual framework for sustainable enterprise development that harmonizes three essential components: economic performance, environmental protection, and social responsibility. This triad forms the basis for long-term value creation and strategic positioning in competitive markets. Particular attention is given to the interdependence between effective competitiveness management and realizing sustainable development goals. The article posits that strategic management practices that enhance competitiveness also directly contribute to the enterprise’s ability to operate responsibly, innovate consistently, and respond flexibly to external changes. It is further argued that the relationship between enterprise development and competitiveness management is fundamental and multidimensional. These two domains are interlinked in conceptual and operational terms. Enterprise development management encompasses long-term strategic goal setting, resource mobilization, technological modernization, innovation management, structural optimization, and proactive adaptation to external challenges. Meanwhile, enterprise competitiveness reflects the organization’s capacity to function efficiently in market conditions, strengthen and expand its market presence, develop unique competitive advantages, and maintain stable profitability over time. This holistic view underscores the necessity of integrating sustainability principles into the core of competitiveness strategies, thus fostering enterprises capable of thriving in the face of future uncertainties.